Integrated Metabolomic and Transcriptomic Analysis and Identification of Dammarenediol-II Synthase Involved in Saponin Biosynthesis in Gynostemma longipes - Ye, Shuang; Feng, Lei; Zhang, Shiyu; Lu, Yingchun; Xiang, Guisheng; Nian, Bo; Wang, Qian; Zhang, Shuangyan; Song, Wanling; Yang, Ling; Liu, Xiangyu; Feng, Baowen; et al. (Frontiers in Plant Science, 2022)
Gynostemma longipes contains an abundance of dammarane-type ginsenosides and gypenosides that exhibit extensive pharmacological activities. Increasing attention has been paid to the elucidation of cytochrome P450 monooxygenases (CYPs) and UDP-dependent glycosyltransferases (UGTs) that participate downstream of ginsenoside biosynthesis in the Panax genus. However, information on oxidosqualene cyclases (OSCs), the upstream genes responsible for the biosynthesis of different skeletons of ginsenoside and gypenosides, is rarely reported. Here, an integrative study of the metabolome and the transcriptome in the leaf, stolon, and rattan was conducted and the function of GlOSC1 was demonstrated. In total, 46 triterpenes were detected and found to be highly abundant in the stolon, whereas gene expression analysis indicated that the upstream OSC genes responsible for saponin skeleton biosynthesis were highly expressed in the leaf. These findings indicated that the saponin skeletons were mainly biosynthesized in the leaf by OSCs, and subsequently transferred to the stolon via CYPs and UGTs biosynthesis to form various ginsenoside and gypenosides. Additionally, a new dammarane-II synthase (DDS), GlOSC1, was identified by bioinformatics analysis, yeast expression assay, and enzyme assays. The results of the liquid chromatography–mass spectrometry (LC–MS) analysis proved that GlOSC1 could catalyze 2,3-oxidosqualene to form dammarenediol-II via cyclization. This work uncovered the biosynthetic mechanism of dammarenediol-II, an important starting substrate for ginsenoside and gypenosides biosynthesis, and may achieve the increased yield of valuable ginsenosides and gypenosides produced under excess substrate in a yeast cell factory through synthetic biology strategy.